Homi Jehangir Bhabha on Indian science and the atomic energy programme : A selection - Bhabha, Homi Jehangir (Mumbai Tata Institute of Fundamental Research, 2009)
Homi Bhabah's ideal of science was profoundly interviewed with the ideal of a better world. He knew that science had the potential to transform live.
Keywords: Homi Bhabha; Growing science; Allocation of Scientfic Research; Science development; Atomic energy